Acetaldehyde Is a Causal Agent Responsible for Ethanol-Induced Ripening Inhibition in Tomato Fruit. - Beaulieu, J. C. (1997)
Inhibition of tomato (Lycopersicon esculentum Mill.) fruit ripening by exogenously applied ethanol was shown to be caused by elevated endogenous levels of acetaldehyde (AA). Exposure of excised pericarp discs of mature-green tomato fruit to ethanol or AA vapors produced elevated levels of both compounds in the tissue, but only the levels of AA were associated with ripening inhibition. Ripening inhibition was dependent on both the applied concentration and the duration of exposure. Discs treated with inhibitory levels of AA had levels of ethanol that were elevated but below that associated with inhibition of ripening. The in vivo activity of alcohol dehydrogenase was inhibited 40 to 60% by 4-methylpyrazole (4-MP), a competitive inhibitor of this enzyme. The inhibitory effect of ethanol on ripening was reduced by the simultaneous application of 4-MP. Tissue treated with 4-MP plus AA vapors had higher endogenous levels of AA and ripening was inhibited longer than in tissue without 4-MP. The tissue AA level resulting from ethanol or AA application appears to be the critical determinant of ripening inhibition.